Demetrius Ducas and the Erotemata Chrysolorae edition (1514), between Venice and Alcalá de Henares - Curnis, Michele (ΠΗΓΗ/FONS, 2019)
In the first Greek book published by Demetrios Ducas when he was professor at the University of Alcalá de Henares (Erotemata Chrysolorae, 1514), there is a gnomological section that coincides with the Planudean version of the Menandri Sententiae. In this article we proceed to the collation of the gnomological section with the text of the editio Aldina (1512), proposing in both cases the editorial responsibility of Ducas. In the second part of the article the fortune of the first Greek grammar manual printed in Spain is examined, thanks to the ownership notes of some copies from the Biblioteca Nacional in Madrid.
Keywords: Demetrios Ducas; Erotemata Chrysolorae; Diego Hurtado de Mendoza; Cardinal Ximenes; Aldus Manutius; Menandri sententiae; gnomological literatura